2015
DOI: 10.1007/s11010-015-2468-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen on expression of prohibitin in white adipose tissue and liver of diet-induced obese rats

Abstract: Prohibitin (PHB) is a ubiquitously expressed and highly conserved protein that participates in diverse cellular processes, and its functions are linked to a variety of diseases. In the present study, to explore transcriptional activation and signaling pathways involved in PHB regulation in response to sex hormone treatment, we investigated the effects of estrogen (17-β-estradiol, E2) on regulation of PHB in several metabolic tissues from male and female rats. Elevated expression of PHB was prominent in white a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
4
1
Order By: Relevance
“…Also, a higher concentration of 10 −6 M E 2 reduced both prohibitin and ERα36 protein expression levels and their association in ht-UtLM cells. The difference in the responses to E 2 observed in our study compared to that reported [ 22 ] may due to the unique cell types or concentrations of E 2 used. The presence of ERα36 in mitochondria and its association with the mitochondrial protein prohibitin suggests that ERα36 may mediate critical roles in maintaining mitochondrial structure and function.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Also, a higher concentration of 10 −6 M E 2 reduced both prohibitin and ERα36 protein expression levels and their association in ht-UtLM cells. The difference in the responses to E 2 observed in our study compared to that reported [ 22 ] may due to the unique cell types or concentrations of E 2 used. The presence of ERα36 in mitochondria and its association with the mitochondrial protein prohibitin suggests that ERα36 may mediate critical roles in maintaining mitochondrial structure and function.…”
Section: Discussioncontrasting
confidence: 88%
“…It is reported that prohibitin 2 binds to the ligand binding domain of ERα66 and represses its transcriptional activity [ 16 ]. It has been shown that E 2 stimulates prohibitin expression in white adipose tissue and in the liver of rats [ 22 ]. In a cell culture model (3T3-L1 and C9 cells), transcription and protein levels of prohibitin were also dose-dependently increased by E 2 treatment, further supporting in vivo data that prohibitin expression may be regulated by estrogens and intracellular steroid hormone signaling pathways [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al has demonstrated that prohibitin is an estrogen-regulated gene in vitro and vivo , and its expression is induced by estrogen in the uterus 14. Similar result has been observed in white adipose tissue and liver, and the estrogen-elevated prohibitin may mediated by estrogen receptor 15. These results suggest that prohibtin involves in estrogen signaling.…”
Section: Introductionmentioning
confidence: 61%
“…Of note, Mito-Ob mice started to gain weight during puberty, indicating a relationship between gonadal sex steroids and the observed phenotypes. Emerging evidence from other laboratories also supported a role of PHB in modulating sex steroid actions in a variety of cells and tissues, as well as PHB as a downstream target of sex steroids [ 15 17 ]. Specifically, the effect of sex steroids on adipocytes, the site of PHB overexpression in Mito-Ob mice, may contribute to the sex-dimorphic metabolic characteristics described.…”
Section: Introductionmentioning
confidence: 99%